Fetal Splenomegaly: A Review. Issue 1 (March 2018) - Moreira, Marta; Brás, Rafael; Gonçalves, Daniela; Alencoão, Inês; Inocêncio, Gonçalo; Rodrigues, Maria; Braga, Jorge
Abstract : Abstract: Enlargement of the fetal spleen is usually found secondary to systemic diseases and is frequently associated with hepatomegaly. By far, the most common causes of fetal splenomegaly are infectious. Other etiologies responsible for this sign are hemolytic anemia, congestive cardiac failure, metabolic disorders, and rarely, leukemia, lymphoma, and histiocytosis. We report a case of prenatal splenomegaly diagnosed at 35 weeks, confirmed in the postnatal period. The postnatal workup showed the newborn had a familial type 3 form of hemophagocytic lymphohistiocytosis (HLH). Hemophagocytic lymphohistiocytosis is an aggressive and life-threatening syndrome of excessive immune activation. The genes implicated in the hereditary forms of the disease act in an autosomal recessive fashion.